Refiring performance of calcium aluminoborosilicate-based dielectrics - Choi, Ik Jin; Park, Jae Gwan; Cho, Yong Soo (WILEY, 2008)
Two dielectric materials consisting of a zinc calcium aluminoborosilicate glass with either an Al2O3 or a CaTiO3 filler were selected to investigate the sensitivity of refirings at a fixed temperature of 850 degrees C to the final physical and dielectric performance. The property changes with refirings depended on the type of filler material and the number of refirings. For example, crystallization of the unexpected ZnAl2O4 phase was found to progress further on increasing the number of refirings in the case of the Al2O3 filler sample. The five refirings of the sample resulted in a decrease of the dielectric constant from 8.46 to 8.06 at 1 MHz. The case of the CaTiO3 filler can be highlighted with the opposite increasing effect of the dielectric constant as the crystalline CaTiSiO5 phase evolved further with refirings.
Keywords: PARTICLE-SIZE; TEMPERATURE